2023
DOI: 10.1136/jitc-2022-005640
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of PexaVec in combination with immune checkpoint inhibition in refractory metastatic colorectal cancer

Abstract: BackgroundOncolytic immunotherapy represents a unique therapeutic platform for the treatment of cancer. Here, we evaluated the safety and efficacy of the combination of pexastimogene devacirepvec (PexaVec) plus durvalumab (anti-programmed death ligand 1) with and without tremelimumab (anti-cytotoxic T-lymphocyte associated protein 4) in patients with standard chemotherapy refractory mismatch repair proficient (pMMR) metastatic colorectal cancer (mCRC) in a phase I/II trial.MethodsAdult patients with histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
0
11
1
Order By: Relevance
“…The normalized data was further analyzed using Gene Set Variation Analysis (GSVA) 41 . Furthermore, CIBERSORTx was performed to estimate the proportion of immune cells in a bulk sample as previously described 36 . The TPM gene expression matrix output by RSEM was reformatted to include only gene symbols.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The normalized data was further analyzed using Gene Set Variation Analysis (GSVA) 41 . Furthermore, CIBERSORTx was performed to estimate the proportion of immune cells in a bulk sample as previously described 36 . The TPM gene expression matrix output by RSEM was reformatted to include only gene symbols.…”
Section: Methodsmentioning
confidence: 99%
“…34,35 2.4.1 | Bulk RNA-seq and data analysis RNA was extracted from fresh-frozen needle biopsy tumor samples at baseline and post-treatment as previously described. 36 Libraries were prepared using the NEBNext® Ultra™ II Directional RNA Library Prep Kit for Illumina, using the 100 or 5 ng protocols based on RNA availability at the CCR Sequencing Facility. Samples with <5 ng RNA ("low concentration") were prepared using the 5 ng protocol.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Gating strategies were performed as previously described. 22 The populations from either live, CD45+leukocytes (for immune profiling) or live, CD3+lymphocytes (for T-cell profiling) were then down sampled and exported as .csv files. After import of these .csv files, graph-based clustering and UMAPs (or Uniform Manifold Approximation and Projection) were generated using the Partek Flow software pipeline (Build V.10.0.22.0703, Partek, St. Louis, Missouri, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The combined treatment with PexaVec, durvalumab, and tremelimumab exhibited promising clinical efficacy in individuals with pMMR mCRC. However, additional investigations are required to ascertain the corresponding predictive biomarkers ( 37 ). Another study showed that the combination of bevacizumab and FOLFOX with durvalumab, a PD-L1 inhibitor, and oleclumab, an anti-CD73 mAb, modestly improved response rates but did not confer any PFS advantage over standard-of-care treatment alone ( 200 ).…”
Section: Immune Checkpoints: Biological Aspects and Clinical Studiesmentioning
confidence: 99%